Management of Vitiligo Through Ayurvedic Modalities: A Case Report - Patel, Satya Prakash; Yadav, Sujata (International Research Journal of Ayurveda & Yoga, 2022)
Vitiligo is a skin depigmentation disease. Approximately 1% of the world’s population is affected. Vitiligo affects both men and women equally, with no racial differences. The majority of instances occur between the second and third decades of life and are acquired. It is a prevalent autoimmune condition with significant socioeconomic and medical implications. Vitiligo has a significant influence on patients’ quality of life; many Vitiligo patients feel stigmatized and unhappy as a result of their condition. It’s characterized by white spots on the skin caused by a lack of melanocytes. In Ayurveda, it is associated with Shvitra or Sweta Kushta. Modern medical sciences are still unable to cure this disease with safe, cost-effective, and efficient medication. Ayurveda offers a lot of potentials when it comes to treating autoimmune skin problems. Here is an instance of vitiligo that was treated with Ayurvedic medicine. We describe a 40- year-old female with vitiligo that has remained stable. In Ayurveda, Panchakarma and shaman chikitsa are used to treat shvitra kushta. Present Vitiligo case was treated with Ayurvedic medicine, which included oral medications such as Arogyavardhini Vati, Kaishor Guggulu, Navayasa Lauha, Khadirarishta, and the local application of Brihat Marichyadi Tailam.